Un carrefour routier au cœur du Jura méridional (Bugey, Ain) du ve au xviiie siècle : morphologie, modelés et itinéraires - Alain Mélo (Archéologie Médiévale)
The morphological analysis of the road network in a small central plain in southern Jura (Bugey, Ain) revealed a reorientation of the main traffic route through the mountains. Roads on a north-south axis conducted the traffic, on the one hand, between Lyon and high Jura, a road used by the monks of Saint-Claude in the 5th and 6th centuries, and, on the other hand, between Belley and Lons-le-Saunier, a path through which Charles the Bald’s body was carried in 877, between the pass of Mont-Cenis (Savoie) and Saint-Denis-en-France. Since the 14th century, the traffic, which was essentially mercantile, is reoriented on an east-west axis, following firstly the development of the fair of Geneva (in the east), and then the fair of Lyon (in the west) during the second half of the 15th century. These major traffic flows have remained unchanged until today with the creation of a strong local network of royal roads as soon as 1740.